Issue Mapping for an Ageing Europe - Rogers, Richard (Amsterdam University Press, 2015)
Issue Mapping for an Ageing Europe is a seminal guide to mapping social and political issues with digital methods. The issue at stake concerns the imminent crisis of an ageing Europe and its impact on the contemporary welfare state. The book brings together three leading approaches to issue mapping: Bruno Latour's social cartography, Ulrich Beck's risk cartography and Jeremy Crampton's critical neo-cartography. These modes of inquiry are put into practice with digital methods for mapping the ageing agenda, including debates surrounding so-called 'old age', cultural philosophies of ageing, itinerant care workers, not to mention European anti-ageing cuisine. Issue Mapping for an Ageing Europe addresses an urgent social issue with new media research tools.